Modelling of plasma flow in curvilinear duct - Moiseenko, V.E.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2002)
The plasma flow in a curvilinear duct is modelled using particle-in-cell method in the cylindrical geometry. The curvature of magnetic field lines in the duct is simulated introducing centrifugal force acting on ions. The electrons are assumed magnetized while the action of the steady magnetic field on the ions is neglected. The electric potential is calculated self-consistently. First the case when drift of the electrons is negligibly small is studied. There, starting from the certain plasma density, equilibrium can exist. It could be reached after some number of ions leaves the plasma column forming the potential well for the ions in the plasma core. An important point is that, at the equilibrium state, the distribution of electric potential is essentially asymmetrical. To avoid the high voltage plasma oscillations the found equilibrium is used as the initial condition for further calculations with finite steady magnetic field. The calculations show that the distribution of the electric field in the plasma duct remains asymmetrical. This causes the electrons to drift to the wall of the duct mainly in vertical direction.